THE ROLE OF INFORMATION COMMUNICATION TECHNOLOGIES IN TECHNOLOGY CLASSES - Z. I. Jurayeva; G. S. Xoshimova (Web of Journals Publishing, 2023)
This article discusses the use of information technology in organizing practical workshops on the technology of processing materials in general secondary schools.
Keywords: technology lessons, reader, information communication technologies, foundation structure, modeling, skirt,